An analysis of ammonia synthesis by the model of Selective Energy Transfer (SET) - Ragnar Larsson (Annals of Mathematics and Physics - Peertechz Publications, 2019)
The SET theory implies that energy is transferred from the catalyst system via infrared radiation to the molecules that are supposed to react. In previous investigations it has been demonstrated that the activation of the reacting species-as long as the molecules are infrared active-can occur at low adsorption strength. However, for molecules that are IR inactive, e.g. dinitrogen, this is not possible. Hence the N2 molecule has to be adsorbed on the catalyst surface to give rise to vibrations that can interact with IR quanta of the catalyst.